2008
DOI: 10.1136/hrt.2007.116392
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac CT and CT coronary angiography: technology and application

Abstract: Multislice computed tomography (MSCT) is an additional potential tool for the assessment of coronary artery disease. It can provide information about stenoses in coronary arteries and coronary artery bypass grafts, ventricular size and function, cardiac structure and masses, pulmonary vein anatomy, myocardial perfusion and coronary artery plaque. In this review the recent developments in CT technology that have made cardiac imaging possible are examined and the benefits of the latest 64-slice and dual-source C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 89 publications
0
58
0
1
Order By: Relevance
“…Clear patterns of vulnerable plaques (rupture versus erosion) were, however, not identified in postmortem CT nor in CT angiography in this series. This is also true in clinical practice as traditional CT-angiography is insensitive for the detection of plaques as the resolution is insufficient to visualize this lipid-rich core and fragile rupture-prone fibrous cap which is responsible for plaque rupture, inflammation, and neovascularisation [2]. The identification of patients with vulnerable plaques is difficult and the combination of several sophisticated imaging methods (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear patterns of vulnerable plaques (rupture versus erosion) were, however, not identified in postmortem CT nor in CT angiography in this series. This is also true in clinical practice as traditional CT-angiography is insensitive for the detection of plaques as the resolution is insufficient to visualize this lipid-rich core and fragile rupture-prone fibrous cap which is responsible for plaque rupture, inflammation, and neovascularisation [2]. The identification of patients with vulnerable plaques is difficult and the combination of several sophisticated imaging methods (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive coronary angiography is currently the ''gold standard'' for assessing coronary artery stenosis, although it has been associated with serious complications [2]. Cardiac multi-detector computed tomography (MDCT), including contrast-enhanced MDCT coronary angiography, is considered a powerful diagnostic tool for the assessment of coronary disease in acute and in chronic cases [3].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in measurements may be partially explained by the spatial resolution of the two imaging techniques. While a 64-slice MDCT scanner has a spatial resolution of 0.4 mm [16], twodimensional echocardiography typically has a spatial resolution of 1.5 mm and variable depending on the frequency of the probe [17]. Thus, at these arterial diameters, the measurements obtained from MDCT will have greater accuracy than TTE.…”
Section: Discussionmentioning
confidence: 99%
“…DSCT improves imaging quality because of less heart rate dependency and offers a spatial resolution of 0.4 mm and a temporal resolution of 83 ms [34]. Busch et al [36] compared 64-slice MSCT and DSCT with cardiac catheterization and showed a good correlation of grading stenoses between the software-assisted evaluation and the results of the coronary catheter angiography.…”
mentioning
confidence: 99%
“…Therefore, the results are highly dependent on subjective factors inherent in the examiner. New software tools for semi-quantitative analysis (CT-QCA, quantitative coronary assessment) might be adequate to improve the diagnostic accuracy und reproducibility [6,34]. However, also for the automated quantitative analysis of the coronary arteries high image quality is required.…”
mentioning
confidence: 99%